The role of galectins in the initiation, amplification and resolution of the inflammatory response - Rubinstein, Natalia (2004)
Inflammation involves the sequential activation of signalling pathways leading to the production of both pro-inflammatory and anti-inflammatory mediators. Galectins constitute a family of structurally related beta-galactoside-binding proteins, which are defined by their affinity for poly-N-acetyllactosamine-enriched glycoconjugates and sequence similarities in the carbohydrate recognition domain. By crosslinking specific glycoconjugates, different members of the galectin family behave as pro-inflammatory or anti-inflammatory agents, acting at different levels of acute and chronic inflammatory responses. Recent studies highlighted immunomodulatory roles for galectins in vivo in several experimental models of chronic inflammation, suggesting that these carbohydrate-binding proteins may be potential targets for the design of a novel generation of anti-inflammatory agents. In this study, we review recent advances on the role of galectins in the initiation, amplification and resolution of the inflammatory response. In particular, we examine the influence of individual members of this family in regulating cell adhesion, migration, chemotaxis, antigen presentation, immune cell activation and apoptosis. From a better understanding of the molecular basis of galectin-induced immune regulation, we may become able to exploit the potential of these sugar-binding proteins and their glycoligands as suitable therapeutic agents in acute and chronic inflammatory disorders.